City-life no more?: Young adults’ disrupted urban experiences and their digital mediation under Covid-19 - Kaufmann, Katja; Straganz, Christoph; Bork-Hüffer, Tabea (Urban planning, 2020)
The Covid-19 pandemic temporarily, yet significantly, reshuffled the position, functions and (mediated) constructions of cities and urban places. The national lockdown, implemented by Austria on 16 March 2020, turned cities overnight from centres of hybrid cultural, economic, social, political life and power to places where urban life(styles) were put on hold. This article begins by presenting first key results of a longitudinal study with young adults studying in educational institutions in the state of Tyrol through the harshest country-wide lockdown measures and their gradual withdrawal. We analyse how participants coped with the disruption of their urban lives and lifestyles and the strategies they employed to compensate. We highlight three main insights. First, participants who had originally migrated to the city from their (often rural) hometowns largely returned to join their families. From there, no longer being an object of physical experience, the city became a digitally imagined, constructed and communicated place, reiterating public discourses that condemned the city as a place where lockdown measures were breached, and the virus spread unchecked. Second, where possible and adapted to the affordances of digital media, students shifted their previous lifestyles to digital space as well as created innovative ways of socialising digitally—thus producing alternative digital forms of urban lifestyles and digitally-mediated urban experiences. Third, during the lockdown period, the importance, use intensity as well as a variety of digital media peaked tremendously. This trend, however, was short-lived as yearned-for offline sociability largely returned to the city once measures were relaxed, leaving those in rural homes detached from their urban peers.
Gesehen am 17.04.2024